Association Between Weight Loss and Improvement of Ventricular Systolic Function in Advanced Heart Failure. Issue 4 (14th February 2013) - Guglin, Maya; Verma, Sameer; Chen, Ren
Abstract : In heart failure (HF), longitudinal changes in ventricular ejection fraction are poorly studied. The authors' objective was to document the dynamic changes in systolic function of both ventricles during acute HF and after a 3‐month follow‐up period, and to identify factors associated with ventricular improvement. A limited access dataset from the Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheterization Effectiveness (ESCAPE) trial provided by The National Heart, Lung, and Blood Institute was analyzed. In patients admitted to the hospital with acute HF, both ventricles were evaluated by echocardiography on admission, at discharge, and at 3 months. From baseline to 3 months, left ventricular ejection fraction (LVEF) increased in 43.4% of patients, decreased in 23.9%, and remained unchanged in 32.7%. Similarly, right ventricular systolic function improved in 40.9%, deteriorated in 25.0%, and remained stable in 34.1%. Weight loss during index admission and cardiac index/cardiac output increase were the only factors associated with LVEF improvement from baseline to month 3. There was no difference between ischemic and nonischemic etiology. In acute HF, ischemic or nonischemic, systolic function of the ventricles improved during 3 months in about 40% of patients and remained unchanged or deteriorated in the rest. Weight loss and increase in cardiac index/output during hospitalization was associated with improvement in LVEF.